Kebutuhan Sarana Dan Prasarana Ditinjau Dari Tipologi Kawasan di Pulau Kodingareng - Nurhidayat M; Fathurrahman Burhanuddin (LOSARI Jurnal Arsitektur, Kota dan Permukiman, 2022)
The spatial planning of the island region has its own challenges. One of the challenges faced in island area planning is the availability of adequate facilities and infrastructure to support community activities on the island. The need for these facilities and infrastructure is an important part of the island's spatial planning. Kodingareng Island is one of the islands in the Sangkarrang Islands District, Makassar City. As one of the island villages in the city of Makassar, of course, Kodingareng Island requires the availability of adequate infrastructure to support community activities. This study aims to determine the need for facilities and infrastructure, especially those that are a priority needed by the community based on the typology of the island of Kodingareng. This study uses an analytical method approach to observing the typology of the island's typology, facilities and infrastructure on the island of Kodingareng and conducting interviews with the community to get an overview of the facilities and infrastructure needed by the community. This study also uses the Analytical Hierarchy Process (AHP) method to determine the priority of facilities and infrastructure needed by the community in supporting their activities. The results of this study are expected to be input for the government in making policies for the development of facilities and infrastructure needed by the community on the island of Kodingareng.